2015
DOI: 10.3920/jiff2014.0006
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of common catfish (Ameiurus melas Raf.) fingerlings fed mealworm (Tenebrio molitor) diet

Abstract: A pre-fattening trial was performed to evaluate the effect of replacement of fishmeal (FM) with insect meal (IM, Tenebrio molitor) on growth performance and survival rate of common catfish (Ameiurus melas). Fingerlings of A. melas (mean body weight, 0.248±0.07g) were randomly distributed over 4 indoor tanks of 2 m3 at a density of 2,000 fish/tank, and kept at a temperature of 23-25°C in two separated recirculating aquaculture systems (RAS). Fish were divided into two groups (two tanks per group): FM and IM. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 28 publications
10
55
0
2
Order By: Relevance
“…Regarding fish, some trials have been carried out with various fish species to evaluate the use of diets containing different insect meals, often used as FM substitutes (Fasakin et al, 2003;St-Hilaire et al, 2007b;Sealey et al, 2011;Alegbeleye et al, 2012;Kroeckel et al, 2012;Oso and Iwalaye, 2014;Roncarati et al, 2015). The results of these trials confirm the possibility of insect meals inclusion in aquaculture feeds, even though there could be some limits related to both insect and fish species (Henry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding fish, some trials have been carried out with various fish species to evaluate the use of diets containing different insect meals, often used as FM substitutes (Fasakin et al, 2003;St-Hilaire et al, 2007b;Sealey et al, 2011;Alegbeleye et al, 2012;Kroeckel et al, 2012;Oso and Iwalaye, 2014;Roncarati et al, 2015). The results of these trials confirm the possibility of insect meals inclusion in aquaculture feeds, even though there could be some limits related to both insect and fish species (Henry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In African catfish (Clarias gariepinus) Ng et al (2001) demonstrated that an inclusion up to 35% of TM meal (up to 80% replacement of the dietary fish meal component in the experimental diets) still maintained growth performances similar to those achieved using fishmeal diets. Nevertheless when fish have different nutritional requirements (i.e., for juveniles), the results may change, as noted by Roncarati et al (2015) who observed a reduction of weight growth and an increase of mortality in com-mon catfish (Ameiurus melas) fingerlings fed TM larvae meal containing diets. In European sea bass (Dicentrarchus labrax) juveniles, data showed that an inclusion of 25% TM larvae meal did not affect growth performances while a higher inclusion level (50%) compromised the weight gain (Henry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tenebrio molitor larvae meal (TM) has been used in broiler De Marco et al, 2015;Biasato et al, 2016) and laying hens (Giannone, 2003;Wang et al, 2005). In fish, TM was used in African catfish (Ng et al, 2001), rainbow trout , and European sea bass , black bullhead (Roncarati et al, 2015) with encouraging results.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, common catfish (Ameiurus melas Raf.) fingerlings and African catfish, C. gariepinus, grew slower when large proportions of the fish meal were replaced (Ng et al 2001;Roncarati et al 2015).…”
Section: Insects Replacing Fish Meal As Feedmentioning
confidence: 99%